Prevalence of third molar impaction in patient with mandibular anterior teeth crowding - Wei, Tan Chun; Soeria Soemantri, Eky Setiawan; Sunaryo, Iwa Rahmat (Universitas Padjadjaran, 2016)
Introduction: Third molar impaction has been a controversial topic among clinician when it comes to mandibular anterior teeth crowding. The aim is to know the prevalence of third molar impaction in patient with mandibular anterior teeth crowding in Orthodontic Department, RSGM UNPAD, Indonesia. Methods: This was a descriptive research, with non-probability sampling obtained from a population with full arch 32 teeth. Totaling 54 samples from year 2011 to 2014 were obtained. The age of sample range from 15 to 25 years old. Also all panoramic radiographs taken from the year 2011 to 2014 were examined using a computer. The position of third molars were determined by Winter’s classification using angle formed between the intersected longitudinal axes of the second and third molars and anterior teeth status by using Little’s irregularities index. Results: This study obtained data that as much as 68.52% mesioangular third molar, 19.44% distoangular, 4.63% horizontal, 1.85% buccolingual and 0% others. In mesioangular impaction condition there was crowding 83.78%, in distoangular condition there was 100% crowding, in horizontal position crowding found 100%, while at buccolingual crowding found 100%.Conclusion: In all positions the third molar impaction was accompanied by crowding of the mandible anterior teeth, with the largest percentage of impaction was the mesioangular position